Sistem Informasi Desa (SID) Terong Based on Community: Towards a Personal Archive Service Model - Susanti, Titi (UI Scholars Hub, 2018)
This article analyzes the process of making Sistem Informasi Desa (SID) based on community established in Terong Village, Dlingo, Bantul district, Yogyakarta. This program is known as the basic administrative system that has compiled the system based on the potential and the needs of society to access public (services). This study uses qualitative research methods. Data are collected through observation, interviews and literature review. Meanwhile, the data analysis carried out through, (1) data reduction, (2) data presentation, and (3) conclusion/verification. The data triangulation technique is used in validation phase in order to make the results are credible. The results showed that the Sistem Informasi Desa (SID) has a significant impact to community in Terong Village. It can not be separated from the capital owned by the citizen due to it has grown well after getting workshop, direction and training from COMBINE Resource Institution. However, the management of SID is not considered maximal because it has not been developed according to current SID development in other regions. The effort to improve the system and the administrative data needs to be done continuously to develop SID. It is in accordance to the development of the village both in social and economiccultural (aspect). Human resource development as SID program manager must also be able to develop SID features based on community information necessity.